2022
DOI: 10.3390/pr10122492
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Removal of Radionuclide Cesium from Water by Biodegradable Magnetic Prussian Blue Nanospheres

Abstract: As the main component of radioactive wastewater, the cesium ion has seriously endangered the environment and human health. Prussian blue nanoparticles (PB NPs) are used as adsorbents for the purification of cesium-containing wastewater because of their ability to selectively adsorb cesium ions. In this work, novel magnetic Prussian blue nanospheres (MPBNs) were developed from polylactic acid nanospheres as a carrier, loaded with Fe3O4 nanoparticles (Fe3O4 NPs) inside and PB NPs outside for the removal of cesiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Generally, at low pH values, competition of metal ions with H + ions in the solution may occur [ 48 ]. At the same time, relatively high efficiency of silver ion removal at pH 2.0 can be explained by their binding to amino groups [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, at low pH values, competition of metal ions with H + ions in the solution may occur [ 48 ]. At the same time, relatively high efficiency of silver ion removal at pH 2.0 can be explained by their binding to amino groups [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using the three-factor simplex central plan, mathematical models (7), (8) and isoparametric surfaces of response functions (Fig. 4) of the influence of the varied factors on changes in the radiation activity of composites after 7 and 28 days of curing:…”
Section: Resultsmentioning
confidence: 99%
“…The most common methods of cesium ion extraction are adsorption, ion exchange, chemical precipitation, chemical reduction, membrane technologies, coagulation, extraction, ion flotation [3][4][5][6]. Adsorption methods have become the most widely used in liquid radioactive waste decontamination technologies due to a wide range of adsorbents, process efficiency, simple technology and a wide range of applications [7]. The most effective sorbents for cesium extraction are ferrocyanide sorbents (synthetic materials based on iron (III), nickel (II), copper (II) and other metals or their mixtures) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study Feng et al (2023) used Prussian blue nanoparticles-PLA mixtures as adsorbents for the treatment of cesium-containing wastewater and investigated the adsorption thermodynamics, kinetics, and isotherm models [42]. It was found that at 293 K cesium ion adsorption capacity was 16.5 mg g -1 and that the metal ion concentration was reduced from 40 mg L -1 to 4.8 mg L -1 .…”
Section: Polylactic Acids Adsorption Studiesmentioning
confidence: 99%